Acute Hepatitis and Renal Failure Related to Intranasal Buprenorphine Misuse: Case Report and Analysis of Cases Reported to the French Network for Drug Monitoring. (December 2013) - Eiden, Céline; Ripault, Marie-Pierre; Larrey, Dominique; Faillie, Jean-Luc; Pinzani, Véronique; Pageaux, Georges-Philippe; Peyrière, Hélène
Background: Rare cases of acute hepatitis have been reported following injection, overdose, and even during the use of buprenorphine (BPN) at therapeutic doses, especially in carriers of hepatitis C virus (HCV).Objectives: To report a case of acute hepatitis and renal failure related to intranasal BPN misuse in a HCV-negative patient and to analyze cases reported to the French postmarketing surveillance system (PMSS) of drugs and in the literature.Methods : All cases of hepatitis related to BPN reported to PMSS between January 1996 and December 2012 were analyzed.Results: A 42-year-old man with a history of intranasal BPN misuse (8 mg/d) for at least 10 years was admitted for flu-like symptoms and abdominal pain. At admission, the patient consumed alcohol, cannabis, and tobacco. Acute hepatitis and acute renal failure were diagnosed . Clinical signs and biological parameters resolved within 26 days. An objective causality assessment revealed that an adverse drug reaction (ADR) was possible. In the French PMSS database, 41 cases of suspected BPN-induced hepatitis are reported. In 36.6% of cases, BPN was misused by the intravenous route. In the literature, 16 cases of acute hepatitis related to BPN with or without renal failure are reported. In all cases, patients were HCV carriers. The primary mechanism of BPN-induced hepatitis is a mitochondrial dysfunction, exacerbated by cofactors (HCV, alcohol, and medications).Conclusion: Intranasal misuse of BPN is increasingly frequent. We report here the first documented case of acute hepatitis and renal failure related to intranasal BPN misuse in a patient negative for HCV infection.